C1q/TNF-Related Protein 9 Promotes Revascularization in Response to Ischemia via an eNOS-Dependent Manner - Shukuro Yamaguchi; Rei Shibata; Koji Ohashi; Takashi Enomoto; Hayato Ogawa; Naoya Otaka; Mizuho Hiramatsu-Ito; Tomohiro Masutomi; Hiroshi Kawanishi; Toyoaki Murohara; Noriyuki Ouchi (Frontiers Media S.A., 2020)
Strategies to promote revascularization are valuable for ischemic cardiovascular disease. Although C1q/TNF-related protein (CTRP) 9 is an adiponectin paralog with protective properties against cardiometabolic disorders, the role of endogenous CTRP9 in endothelial function is largely unknown. This study aimed to investigate the effects of CTRP9 on revascularization processes and dissected the potential mechanisms. CTRP9-knockout (KO) and wild-type (WT) mice were subjected to unilateral hindlimb ischemic surgery. CTRP9-KO mice exhibited impaired blood flow recovery and decreased capillary density in the ischemic limb compared with WT mice. In both CTRP9-KO and WT mice, systemic delivery of an adenoviral vector expressing CTRP9 (Ad-CTRP9) accelerated blood flow recovery. Treatment with recombinant CTRP9 protein increased network formation and migration of cultured human umbilical vein endothelial cells (HUVECs). CTRP9 promoted the phosphorylation of AMP-activated kinase (AMPK), Akt, and endothelial nitric oxide synthase (eNOS) in HUVECs. CTRP9-KO mice also showed reduced phosphorylation levels of AMPK, Akt, and eNOS in the ischemic limbs compared with WT mice. Furthermore, blockade of AMPK or Akt signaling pathway reversed the CTRP9-stimulated eNOS phosphorylation in HUVECs. Treatment with the NOS inhibitor significantly reduced CTRP9-stimulated network formation and migration of HUVECs. Of note, Ad-CTRP9 had no effects on blood flow of the ischemic limb in eNOS-KO mice. These results indicated that CTRP9 promotes endothelial cell function and ischemia-induced revascularization through the eNOS-dependent mechanism, suggesting that CTRP9 represents a target molecule for treatment of ischemic vascular diseases.